The Effectiveness of Team Assisted Individualization in Teaching Vocabulary Viewed from Studentsâ Motivation - *, Sulaiman (Proceeding of International Conference on Teacher Training and Education, 2016)
This research reveals an experimental study about the effectiveness Team Assisted Individualization in teaching vocabulary at private university in Pontianak. The population of this research was the first semester students of university in Pontianak. The sample was two classes consisting of 60 students taken by using cluster random The data analysis was done by applying descriptive and inferential statistic (ANOVA and Tukey Test) to test the research hypothesis. Based on the results of the analysis, the findings of this research are: (1) the students who are taught by using Team Assisted Individualization have better vocabulary mastery that those who are taught Peer tutoring. In other word, the use of Team Assisted Individualization is more effective than Peer Tutoring in teaching Vocabulary; (2) the students having high motivation have better vocabulary mastery than those having low motivation; and (3) there is interaction between teaching method and motivation toward studentsâ vocabulary mastery. Based on research findings, it can be concluded that Team Assisted Individualization is an effective teaching method to teach vocabulary for the first semester students of university in Pontianak. The effectiveness of the method is influenced by the studentsâ level of motivation.